The Phenomenology of Testimony : From Inner Truth to Shared World - Heiden, Gert-Jan van der; Marinescu, Paul (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025., 2025)
Testimony is a central topic in contemporary philosophy, with a vast array of disciplines, from epistemology to testimonial literature, demonstrating considerable interest in it. Among these approaches, phenomenology and hermeneutics offer exemplary ways of capturing essential dimensions of testimony that are often overlooked. This volume explores the fundamental issues at stake in such a hermeneutical phenomenology, by developing new insights into the defining role testimony holds in shaping personal identity and human reality in general. By examining how testimony is engaged in the creation of a common world that includes singular experiences, the eleven essays collected here provide thought-provoking questions for other concerned disciplines, including history, sociology, and ecology.